Reliability and Validity of the Traditional Chinese Version of the Advance Care Planning Engagement Survey: A Pilot Evaluation in Taiwanese Outpatients. Issue 3 (July 2022) - Wei, Fang-Chun; Hsu, Chieh-Kuan; Wu, Yu-Lin; Liao, Jung-Yu; Huang, Chi-Hsien; Hsiung, Chao Agnes; Yu, Sang-Ju; Lin, Cheng-Pei; Chen, Ping-Jen
Objective: The Advance Care Planning Engagement Survey (ACP-ES) has proven effective in evaluating individuals' engagement in advance care planning (ACP). However, a Traditional Chinese version of ACP-ES (ACPES-TC) has not yet been developed. Therefore, this study aimed to translate and preliminarily validate the ACPES-TC in the Taiwanese context.Material and Methods: A forward and backward translation process was conducted. The translated questionnaire was confirmed by clinical and academic experts. The ACPES-TC was then evaluated for its reliability and validity with participants in the community and from an outpatient clinic in a medical center in Northern Taiwan. The participants comprised healthy people aged 20 to 30 years and patients ≥55 years old, recruited from September 17 to October 28, 2019.Results: Seventy people were recruited, including 20 people aged 20 to 30 years in the community and 50 patients ≥ 55 years old from clinics. The ACPES-TC scores are significantly higher among those of older age, having financial independence, and under long-term medication ( p  < .05). The patients' preference for health-related decision-making is significantly correlated with the ACPES-TC score; the point-biserial correlation coefficient is 0.46 ( p  < .001). The discriminant and criterion-related validities are verified. The ACPES-TC demonstrated a good internal consistency (Cronbach's α .97), acceptable one-week test-retest reliability (overall intraclass correlation coefficient 0.86), and low practice effect between the test and retest (Cohen's d .43).Conclusion: The overall reliability and validity of the ACPES-TC are fair, which could be used to evaluate the patients' engagement in ACP in Taiwan. However, further studies with a full-scale psychometric evaluation are needed.